The material and the spiritual wealth - Constantin, Andrei; Petrov, George Daniel (Technium Social Sciences Journal, 2023)
Material wealth without virtue, that is, without spiritual wealth, is a loser. Well-being, as the possession of goods, is not an end in itself for our life, but rather a means by which we can also help our fellow men. The writings of the Holy Fathers are rich in references about the equality of people. Wealth is not depicted as a bad thing in itself. It is possible to be rich and still remain a good Christian, that is, to be both materially and spiritually rich. Those who seek to gather material wealth most often become spiritually poor.